2000
DOI: 10.1016/s0008-6363(00)00082-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of oxidative stress by carvedilol: role in maintenance of ischaemic myocardium viability

Abstract: Our data show that the anti-oxidant activity of carvedilol is relevant for the maintenance of myocardium viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 24 publications
2
28
0
1
Order By: Relevance
“…22,23 In our preliminary study using sham-operated rats, the heart rate reduction induced by the present dose of carvedilol (1 mg/kg) was similar to that of propranolol (1 mg/kg) (19.0±8.9%, n=8 vs 18.5±8.0%, n=8). Therefore, the magnitude of -blocking action of carvedilol might be equivalent to that of propranolol in the present study.…”
Section: Propranolol Vs Carvedilolsupporting
confidence: 60%
See 1 more Smart Citation
“…22,23 In our preliminary study using sham-operated rats, the heart rate reduction induced by the present dose of carvedilol (1 mg/kg) was similar to that of propranolol (1 mg/kg) (19.0±8.9%, n=8 vs 18.5±8.0%, n=8). Therefore, the magnitude of -blocking action of carvedilol might be equivalent to that of propranolol in the present study.…”
Section: Propranolol Vs Carvedilolsupporting
confidence: 60%
“…These effects of carvedilol were not different from those of propranolol, suggesting the primary influence of -adrenoceptor blocking action of carvedilol is on tracer kinetics, but not other mechanisms, such as -blocking or antioxidant effects, that have been implicated previously. 22,23 The present results also imply that the efficacy of cardiac FA imaging for the detection of coronary heart disease would not be decreased by treatment with -blockers.…”
Section: Effects Of -Adrenoceptor Blockade On Cardiac Fa Imagingmentioning
confidence: 50%
“…37 Carvedilol, a nonspecific ␤-antagonist with ␣-blocking activity, has antioxidant properties. 38 Calcium channel blockers have also been reported to have antioxidant properties, inasmuch as they inhibit lipid peroxidation by scavenging peroxy radicals. 39 Captopril, an ACE inhibitor, has also been reported to be an OH Ϫ scavenger because of its sulfhydryl content in addition to reduced angiotensin II, which is a potent activator of NADPH oxidase.…”
Section: Pharmacological Perspectivesmentioning
confidence: 99%
“…The antiapoptotic cardioprotective role of Carv is independent of its antiadrenergic properties (Schwarz et al, 2003). Studies have shown that the antioxidant properties of Carv provide it a unique ability to maintain the viability and inhibit apoptosis in the ischemic myocardium (Cargnoni et al, 2000;Carreira et al, 2006). In addition, experimental studies have shown that Carv treatment alleviates left ventricular remodeling, fibrosis, and cardiac dysfunction in rats (Barone et al, 2007;Yoshikawa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%